I Like to Read Comics : Night Light - Emberley, Michael (New York : Holiday House, 2025)
During a blackout, a parent gathers stars to comfort their child, then returns them to the sky, and together they sleep under the stars outside.
Ages 4-8
Keywords: Parent and child -- Fiction; Fear -- Fiction; Graphic novels